Motor Development in Children: Motor Abilities, BMI and Related Factors. What mediation effects? - Monacis, Domenico; Graziano, Giusi; Colella, Dario (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2022)
Sedentary habits and low levels of physical activity limit the motor skills learning, leading to the progressive reduction of the individual motor repertoire and conditioning the development of related factors. Research in motor and sports sciences is still proceeding in a shattered way, not only because of the interdisciplinary connotations, limiting the transformation of scientific evidence into good practices. This study aims to investigate the relationship between body mass index (BMI), motor performance and factors related to the practice of physical activity in a sample of adolescents through the study of mediation factors. The sample is composed of 60 middle school students aged 11-12 (M = 24, F = 36), selected as part of the project "Regional Observatory on Levels of Physical Activity and Motor Development", coordinated by the University of Foggia. The study included the proposal of 4 motor tests (standing long jump, medicine ball throw 2Kg, shuttle run10x5 and Mile) and three questionnaires to evaluate the following factors: levels of physical activity, enjoyment, self-perception. The results showed that the 10x5 shuttle run test is a factor of partial mediation between the BMI and the standing long jump, while the self-perception totally mediates the relationship between enjoyment and the Mile test. The small sample size does not allow for generalization and extension of the results, but it has been possible to deduce some methodological implications for the training of physical education teachers.